Deep or awake removal of laryngeal mask airway in children at risk of respiratory adverse events undergoing tonsillectomy—a randomised controlled trial - Ramgolam, A.; Hall, Graham; Zhang, G.; Hegarty, M.; von Ungern-Sternberg, B. (Oxford University Press, 2018)
Background: Laryngeal mask airways (LMA) are widely used during tonsillectomies. Contrasting evidence exists regarding the timing of the removal and the risk of perioperative respiratory adverse events. We assessed whether the likelihood of perioperative respiratory adverse events is influenced by the timing of LMA removal in children with at least one risk factor for these events. Methods: Participants (n=290, 0–16 yr) were randomised to have their LMA removed either deep (in theatre by anaesthetist at end-tidal sevoflurane >1 minimum alveolar concentration) or awake (in theatre by anaesthetist or in postanaesthesia care unit by anaesthetist or trained nurse). The primary outcome was the occurrence of perioperative respiratory adverse events over the whole emergence and postanaesthesia care unit phases of anaesthesia. The secondary outcome was the occurrence of perioperative respiratory adverse events over the distinct phases of emergence and postanaesthesia care unit. Results: Data from 283 participants were analysed. Primary outcome: even though a higher occurrence of adverse events was observed in the awake group, no evidence for a difference was found [45% vs 35%, odds ratio (OR): 1.5, 95% confidence interval (CI): 0.9–2.5, P=0.09]. Secondary outcome: there was no evidence for a difference between the groups during emergence [19 (14%) deep vs 25 (18%) awake, OR: 0.74, 95%CI: 0.39–1.42, P=0.37]. However, in the postanaesthesia care unit, children with an awake rather than deep removal experienced significantly more adverse events [55 (39%) vs 37 (26%); OR: 1.85, 95%CI: 1.12–3.07, P=0.02]. Conclusion: We found no evidence for a difference in the timing of the LMA removal on the incidence of respiratory adverse events over the whole emergence and postanaesthesia care unit phases. However, in the postanaesthesia care unit solely, awake removal was associated with significantly more respiratory adverse events than deep removal. Trial registration number: ACTRN12609000387224 (www.anzctr.org.au).